Experimental evaluation and field implementation of FRP bridge deck modules - Woraphot Prachasaree; Vimala Shekar (Songklanakarin Journal of Science and Technology (SJST), 2008)
Construction of highway bridge decks using fiber reinforced polymer (FRP) composite deck and superstructuremodules in lieu of concrete decks has proven to be feasible. However, FRPs are not widely accepted yet despite theirbenefits such as non-corrosiveness, higher strength to weight ratio, and better fatigue resistance than conventional materials.Lack of wider usage of FRP material is mainly attributed to the absence of: 1) standardized test procedures, 2) designspecifications, and 3) construction procedures. The higher initial cost is also inhibiting bridge engineers in selecting FRPmodules as highway bridge super structural systems.Implementation of FRP composites technology for highway bridge decks leads to higher safety and lower life cyclecosts. Significant ongoing research and development of FRP deck modules as illustrated herein, has proven to enhancedeck module properties in developing FRP modules with enhanced structural performance.Prodeck 4 is one such multicellular deck that was recently developed, and extensively evaluated for static and fatigueloads, and its response results are presented herein. From rigorous testing, it was concluded that Prodeck 4 could resistAASHTO HS 25 loading with maximum stringer spacing of 48 inches. This led to construction of two bridges (one in Ohioand other in West Virginia) using Prodeck 4 as decking.